Antitumor Activity of Chinese Propolis in Human Breast Cancer MCF-7 and MDA-MB-231 Cells. (22nd May 2014) - Xuan, Hongzhuan; Li, Zhen; Yan, Haiyue; Sang, Qing; Wang, Kai; He, Qingtao; Wang, Yuanjun; Hu, Fuliang
Abstract : Chinese propolis has been reported to possess various biological activities such as antitumor. In present study, anticancer activity of ethanol extract of Chinese propolis (EECP) at 25, 50, 100, and 200  μ g/mL was explored by testing the cytotoxicity in MCF-7 (human breast cancer ER(+)) and MDA-MB-231 (human breast cancer ER(−)) cells. EECP revealed a dose- and time-dependent cytotoxic effect. Furthermore, annexin A7 (ANXA7), p53, nuclear factor- κ B p65 (NF- κ B p65), reactive oxygen species (ROS) levels, and mitochondrial membrane potential were investigated. Our data indicated that treatment of EECP for 24 and 48 h induced both cells apoptosis obviously. Exposure to EECP significantly increased ANXA7 expression and ROS level, and NF- κ B p65 level and mitochondrial membrane potential were depressed by EECP dramatically. The effects of EECP on p53 level were different in MCF-7 and MDA-MB-231 cells, which indicated that EECP exerted its antitumor effects in MCF-7 and MDA-MB-231 cells by inducing apoptosis, regulating the levels of ANXA7, p53, and NF- κ B p65, upregulating intracellular ROS, and decreasing mitochondrial membrane potential. Interestingly, EECP had little or small cytotoxicity on normal human umbilical vein endothelial cells (HUVECs). These results suggest that EECP is a potential alternative agent on breast cancer treatment.